2018
DOI: 10.1182/blood-2017-12-768986
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular coagulation in hematopoietic stem and progenitor cell regulation

Abstract: The hemostatic system plays pivotal roles in injury repair, innate immunity, and adaptation to inflammatory challenges. We review the evidence that these vascular-protective mechanisms have nontraditional roles in hematopoietic stem cell (HSC) maintenance in their physiological bone marrow (BM) niches at steady-state and under stress. Expression of coagulation factors and the extrinsic coagulation initiator tissue factor by osteoblasts, tissue-resident macrophages, and megakaryocytes suggests that endosteal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 103 publications
0
31
0
Order By: Relevance
“…Moreover, the DAMPs Hmgb1 and S100a9 are not only important activators of the ComC in the MBL-dependent pathway but in parallel also trigger activation of the coagulation cascade (CoaC) [ 8 , 13 , 35 ]. To explain this, DAMPs bind to MBL that subsequently triggers mannan-activated serine proteases (MASPs) to activate both ComC and in parallel also CoaC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the DAMPs Hmgb1 and S100a9 are not only important activators of the ComC in the MBL-dependent pathway but in parallel also trigger activation of the coagulation cascade (CoaC) [ 8 , 13 , 35 ]. To explain this, DAMPs bind to MBL that subsequently triggers mannan-activated serine proteases (MASPs) to activate both ComC and in parallel also CoaC.…”
Section: Discussionmentioning
confidence: 99%
“…Hemostasis and coagulation occur as early as 1 hour after implantation and onset of granulation tissue development at the injury site seen within 2 hours . Nguyen et al observed the expression of coagulation factors and extrinsic coagulation initiator tissue factor by osteoblasts. This study further demonstrated the previously unknown regulatory role of such extravascular coagulation factors on the endosteal stem cell niche and the activation of their egress to areas of injury.…”
Section: The Living Bone and The Endosteal‐implant Interfacementioning
confidence: 99%
“…Proteins like factor XI, XII, and prothrombin have been demonstrated in extravascular localizations including atherosclerotic vessels, but whether these are deposited or locally synthesized remains unknown (Borissoff et al 2010;Wilcox 1994;Soardi et al 1961). Of interest, coagulation enzymes including thrombin and aPC participate in the control of hematopoiesis in the bone marrow (Nguyen et al 2018), which may be relevant for the response to stress situations including inflammation. Within atherosclerotic lesions, coagulation proteins like TF and factors VII and X contribute to form catalytic complexes driving thrombin and fibrin formation (Borissoff et al 2010).…”
Section: Coagulation Proteasesmentioning
confidence: 99%